Work disability and state benefit claims in early rheumatoid arthritis: the ERAN cohort - McWilliams, Daniel F.; Varughese, Sneha; Young, Adam; Kiely, Patrick D.; Walsh, David A. (Oxford University Press, 2013)
Objective. RA is an important cause of work disability. This study aimed to identify predictive factors for work disability and state benefit claims in a cohort with early RA.